Use of smartphones by romantic partners to maintain their relationships - Mhora, Glitter (Department of Information Systems, 2021)
PROBLEM STATEMENT: The way we interact in our relationships is continuously changing as technology advances. Technology can be used to enhance or destroy relationships depending on how people manage their use within relationships. Human relationships especially romantic ones are essential as they have an impact on a person's emotional, mental, and physical well-being. Most of the research to date has focused on the quantitative measurement of the advantages and disadvantages of technology as well as on the problematic use of smartphones. Little research has been done on the effect of smartphones on romantic relationship maintenance. THE PURPOSE OF THE RESEARCH: The objective of this research was to find out how individuals in romantic relationships were using their smartphones to maintain their relationships. DESIGN/METHODOLOGY: This research followed an interpretivist qualitative approach. Data was collected firstly through a discussion on Twitter under the hashtag #“RomanticMaintenancewithSmartphones”. This was then followed by fourteen in-depth semi-structured interviews which were done with individuals who were in romantic relationships or had been in a romantic relationship less than six months ago. A combination of purposive, snowballing and convenience sampling techniques were used. The affordance theory was used as a theoretical framework for the research and the data was analysed using thematic analysis. FINDINGS: The study identified individual and interactional affordances of smartphones for romantic relationship maintenances. Relationship thinking, breaking away from reality and displaying intimacy and affection where the individual affordances identified in the study. The interactive affordances were showing support and encouragement, planning and organising, openness for conflict management and displaying transparency. Personal values and culture were seen to have an impact on which affordances of smartphones a person utilised. In addition to maintaining the relationship positively, there were also negative outcomes of the actualization of the affordances of smartphones such as unrealistic expectations created on partners and partner abstraction.